Climate change will likely threaten areas of suitable habitats for the most relevant medicinal plants native to the Caatinga dry forest - Silva, Jéssica Luiza S.; Cruz-Neto, Oswaldo; Tabarelli, Marcelo; Albuquerque, Ulysses Paulino; Lopes, Ariadna Valentina (Ethnobiology and Conservation, 2022)
Disruption of ecosystem services associated with climate change may affect human well-being in different ways. Medicinal plants provide extremely relevant ecosystem services. Here, we tested the hypothesis that highly suitable habitats (i.e. suitability ≥ 0.8) for medicinal plants in Caatinga dry forest may be potentially contracted under scenarios of climate change, which are represented by different levels of increases in greenhouse gas emissions. We performed species distribution modelling to simulate the effects of climate change on the range of suitable habitats for medicinal plants native to the Caatinga dry forest. We selected the 10 most important plant species based on their high local importance as medicinal resources. We documented that climate change may distinctly affect areas of suitable habitats for medicinal plants in the Caatinga dry forest. Independent of the future climatic scenario projected to 2070, 60% of the studied species will likely experience reductions in their areas of highly suitable habitats, 30% will likely experience increases and 10% may not be affected. Specifically, suitable habitats will likely be reduced for Myracrodruon urundeuva, Erythrina velutina, Operculina hamiltonii, Cereus jamacaru, Bauhinia cheilantha, and Anadenanthera colubrina; increased for Amburana cearensis, Neocalyptrocalyx longifolium and Operculina macrocarpa; and may not be affected exclusively for Maytenus rigida in future scenarios of climate change. We alert that potential future contractions of highly suitable habitats for the most important medicinal plants may compromise ecosystem functions and the provisioning of relevant natural medicines, mainly to low-income communities, which predominate abundant in the Caatinga dry forest.